Optimization and validation of singleplex and multiplex RT-qPCR for detection of citrus bark cracking viroid (CBCVd), hop latent viroid (HLVd), and hop stunt viroid (HSVd) in hops (Humulus lupulus L.) - Guček, Tanja; Jakše, Jernej; Radisek, Sebastjan (Plant disease, 2023)
Direct crop losses due to plant diseases and the measures used to control them have significant agricultural and economic impacts. The shift from diverse small-scale to large-scale genetically uniform monoculture production, along with agricultural intensification and climate change, has led to several known epidemics in man-made agroecosystems that have been rendered more vulnerable to pathogens. One such example is hop growing, which is threatened by highly aggressive hop viroids. Since 2007, almost one-third (about 500 ha) of Slovenian hop gardens have been affected by severe hop stunt disease caused by citrus bark cracking viroid (CBCVd), which continues to spread despite strict prevention measures. We have developed and validated a multiplex RT-qPCR (mRT-qPCR) for the sensitive detection of CBCVd, hop latent viroid (HLVd), and hop stunt viroid (HSVd). Singleplex RT-qPCR assays were designed individually and subsequently combined in a one-step mRT-qPCR assay. Hop-specific mRNA170 and mRNA1192 internal controls were also developed to detect possible PCR inhibition. Analytical specificity was tested on 35 samples from different hosts, geographic regions, and combinations of viroids. Method validation showed that mRT-qPCR had lower sensitivity than singleplex RT-qPCR, while specificity, selectivity, repeatability, and reproducibility remained unchanged. The newly developed assays were found to be robust, reliable, and suitable for large-scale screening of hop viroids.